2006
DOI: 10.1109/tnano.2006.869946
|View full text |Cite
|
Sign up to set email alerts
|

Non-quasi-static small-signal modeling and analytical parameter extraction of SOI FinFETs

Abstract: Accurate modeling and analytical parameter extraction of the non-quasi-static small-signal model of FinFETs are presented using a three-dimensional device simulator. Using simple -and -matrices calculations, the extrinsic gate-to-drain/source capacitance and source/drain resistance are de-embedded from the small-signal equivalent circuit. The analytical parameter extractions are performed by -parameter analysis after removing the extrinsic gate-to-drain/source capacitance and source/drain resistance. Accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(25 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…15(a), the variation in the ratio of the extrinsic drain-side parasitic fringing capacitance due to the dual-k spacer C fod [35] and total gate capacitance C gg for different values of k and t sp is presented. It is observed that for lower value of t sp , initially, the ratio (C fod /C gg ) increases and then decreases with k suggesting improvement in gate control, whereas, for higher value of t sp , the ratio monotonically increases with k suggesting gate control degradation due to the parasitic fringing capacitance.…”
Section: B Rf Performance Of Dkau-finfetmentioning
confidence: 99%
See 1 more Smart Citation
“…15(a), the variation in the ratio of the extrinsic drain-side parasitic fringing capacitance due to the dual-k spacer C fod [35] and total gate capacitance C gg for different values of k and t sp is presented. It is observed that for lower value of t sp , initially, the ratio (C fod /C gg ) increases and then decreases with k suggesting improvement in gate control, whereas, for higher value of t sp , the ratio monotonically increases with k suggesting gate control degradation due to the parasitic fringing capacitance.…”
Section: B Rf Performance Of Dkau-finfetmentioning
confidence: 99%
“…The optimization of t sp is performed considering I ON of the device and the corresponding C fod . The C fod is extracted as described in [35]. In order to optimize t sp , initially, t sp = 10 nm is considered as the upper limit since beyond this value of t sp , the improvement in I ON is negligible, as shown in the inset of Fig.…”
Section: Digital Circuit Performance Of Dkau-finfetmentioning
confidence: 99%
“…An accurate Y-parameter analysis from the small signal equivalent circuit is carried out for the extraction of parasitic as well as the intrinsic components. The small signal equivalent circuit for high frequency analysis with the inclusion of the non-quasi static effects is taken from [12] as shown in Fig. 10 where the box represents the intrinsic components with R gs and R gd being the distributed channel resistances, g m and g ds are the transconductance and drain conductance and L sd is the inductance to include the effect of the time constant s m due to the non quasi static effects (NQSs).…”
Section: Rf Analysismentioning
confidence: 99%
“…As reported in [12], the [Y in ] matrix is converted to [Z in ] and source/ drain resistance R s and R d are de-embedded to obtain the pure intrinsic Y-parameter matrix [Y int ]. The channel resistance method was implemented for the extraction of source/drain series resistance with three different values of the overdrive voltage and a value of 10.785 X was obtained.…”
Section: Rf Analysismentioning
confidence: 99%
“…According to the 2016 prediction of the ITRS 2.0 roadmap, FinFETs will continue to follow the scaling trend of CMOS transistors to the 5‐nm technology node and beyond. Considering radio frequency (RF) advances, FinFETs have been considered an attractive candidate for high‐frequency applications . To parallel the process technology and circuit design methodology, a compact model that serves as a link between process technology and circuit design is greatly needed.…”
Section: Introductionmentioning
confidence: 99%